Prototipo de programa computarizado en realidad virtual para la enseñanza de la anatomía cerebral a estudiantes de psicología en la Universidad de la Costa (2019)
The present document seeks to achieve the development of a computational tool for teaching brain anatomy, using virtual learning tools as purpose to facilitate the learning process to college students, incentivizing the use of technological tools in education given the current needs identified in the training area and research laboratories, where activities are carried out for the training of health professionals in the discipline of study, where models and images are used and in some cases, a software, resulting in limitations of knowledge. Therefore, it is proposed to provide students with the description of brain anatomy through virtual learning tools with the purpose of providing improvements to undergraduate education regarding this topic. The project is based on four methodological stages starting with the definition of the requirements for the tool´s design, collecting the required academic components, followed by the definition and selection of the input information, being the basis for the tool´s development. Finally, the validations are carried out and evaluation tests are applied to know the satisfaction of the target audience with respect to the competences acquired in virtual learning in the teaching of cerebral anatomy. The results show that the software has an excellent rate of approbation by the teachers.